Estrategias didácticas multimediales offline para el fortalecimiento de los procesos lecto-escritores de los estudiantes del nivel básica primaria (2019)
The purpose of the research was the configuration of offline multimedia teaching strategies for the strengthening of the reading-writing processes of the students of the primary basic level. It is epistemologically framed in the rationalist-critical approach, framed in the measurement quantitative paradigm, also called positivist, the method used is inductive. This research starts from the assumption that there are valid theories and methodologies in the area of literacy teaching, so the research is purposeful of an applicative nature. In line with this, the systemic design was made up of three operational phases that refer to this: a field phase of an empirical nature which includes the approach to reality based on the application of the survey technique whose instrument was the questionnaire closed with a Likert scale, applied to teachers of Primary Basic Education. The analysis of these data was incorporated in the elaboration of the proposal. It also includes a theoretical-explanatory phase that based the design on the final proactive phase of a heuristic nature. As significant findings, there is the notable acceptance of teachers about the importance of teaching strategies based on multimedia content for the strengthening of literacy skills. To improve this deficit situation, the didactic strategies based on the constructivist vision of Piaget (1920), Vygotsky (1930), Ausubel (1960) and Jonassen (1999) were designed, operationally the functional components described in the curricular guidelines of Colombian Ministry of Education (1994). The use of educational strategies that do not need internet connection, such as interactive presentations, videos, among others, is recommended.